Systematic Organization of COVID-19 Data Supported by the Adverse Outcome Pathway Framework - Nymark, Penny; Sachana, Magdalini; Leite, Sofia Batista; Sund, Jukka; Krebs, Catharine E.; Sullivan, Kristie; Edwards, Stephen; Viviani, Laura; Willett, Catherine; Landesmann, Brigitte; Wittwehr, Clemens (Frontiers in Public Health, 2021)
Adverse Outcome Pathways (AOP) provide structured frameworks for the systematic organization of research data and knowledge. The AOP framework follows a set of key principles that allow for broad application across diverse disciplines related to human health, including toxicology, pharmacology, virology and medical research. The COVID-19 pandemic engages a great number of scientists world-wide and data is increasing with exponential speed. Diligent data management strategies are employed but approaches for systematically organizing the data-derived information and knowledge are lacking. We believe AOPs can play an important role in improving interpretation and efficient application of scientific understanding of COVID-19. Here, we outline a newly initiated effort, the CIAO project (https://www.ciao-covid.net/), to streamline collaboration between scientists across the world toward development of AOPs for COVID-19, and describe the overarching aims of the effort, as well as the expected outcomes and research support that they will provide.